B–H functionalization of the monocarba-closo-dodecaborate anion by rhodium and iridium catalysis. Issue 10 (16th February 2017) - Shen, Yunjun; Pan, Yani; Zhang, Kang; Liang, Xuewei; Liu, Jiyong; Spingler, Bernhard; Duttwyler, Simon
Abstract : The regioselective derivatization of the monocarba- closo -dodecaborate anion via catalytic B–H bond activation is reported. Abstract : The regioselective derivatization of the monocarba- closo -dodecaborate anion via catalytic B–H bond activation is reported. Amide directing groups in combination with rhodium and iridium catalysts allowed for the direct functionalization of cage boron vertices. Products comprising B–C, B–N and B–Cl bonds were synthesized. As a key intermediate of the B–H activation step, an iridium complex with a direct B–Ir interaction was isolated and fully characterized by spectroscopic methods as well as X-ray crystallography.